Missed Opportunities for Loco-Regional Treatment of Elderly Women with Breast Cancer - Bhoo-Pathy, N.; Balakrishnan, N.; See, M.H.; Mohd Taib, N.A.; Yip, C.H. (Springer Verlag (Germany), 2016)
Background: Factors associated with surgery, adjuvant radiotherapy, and chemotherapy and whether there were missed opportunities for treatment in elderly patients were determined in an Asian setting. Methods: All 5616 patients, diagnosed with breast cancer in University Malaya Medical Centre from 1999 to 2013 were included. In 945 elderly patients (aged 65 years and above), multivariable logistic regression was performed to identify factors associated with treatment, following adjustment for age, ethnicity, tumor, and other treatment characteristics. The impact of lack of treatment on survival of the elderly was assessed while accounting for comorbidities. Results: One in five elderly patients had comorbidities. Compared to younger patients, the elderly had more favorable tumor characteristics, and received less loco-regional treatment and chemotherapy. Within stage I–IIIa elderly breast cancer patients, 10 % did not receive any surgery. These patients were older, more likely to be Malays, have comorbidities, and bigger tumors. In elderlies with indications for adjuvant radiotherapy, no irradiation (30 %) was associated with increasing age, comorbidity, and the absence of systemic therapy. Hormone therapy was optimal, but only 35 % of elderly women with ER negative tumors received chemotherapy. Compared to elderly women who received adequate treatment, those not receiving surgery (adjusted hazard ratio: 2.30, 95 %CI: 1.10–4.79), or radiotherapy (adjusted hazard ratio: 1.56, 95 %CI: 1.10–2.19), were associated with higher mortality. Less than 25 % of the survival discrepancy between elderly women receiving loco-regional treatment and no treatment were attributed to excess comorbidities in untreated patients. Conclusion: While the presence of comorbidities significantly influenced loco-regional treatment decisions in the elderly, it was only able to explain the lower survival rates in untreated patients up to a certain extent, suggesting missed opportunities for treatment.